2

1 = 77.18 ∙ 0.031 = 2.39 ;

2 = 248.6 ∙ 0.319 = 79.3 ;

3 = 555.1 ∙ 0.240 = 133.2 ;

4 = 492.5 ∙ 0.15 = 73.8 ;

q1 = 6.75 ;

q2 = 0.9 .

. 19. .

0 ≤ 1 ≤ 0.231 :

). -Q1∙(1) + Y - q∙X1 = 0

Q1∙(1) = Y - q∙X1

Q1∙(0) = Y - q∙X1 = 14.1 0 = -14.1

Q1∙(0.354) = Y - q∙X1 = 14.1 6.75 ∙ 0.231 = 12.54

). 1∙(1) - Y ∙(1)+ q∙X1 ∙( X1/2) = 0

1∙(1) = Y ∙(1) - q∙X1 ∙( X1/2)

1∙(0) =- Y ∙(1) - q∙X1 ∙( X1/2)= 0

1∙(0.231) = Y ∙(1) - q∙X1 ∙( X1/2)= 14.1 ∙(0.231) 6.75∙0.231 ∙( 0.0.231/2)= 3.07

). N1∙(1) - = 0

N1∙(1) = = 230

0.231 ≤ 2 ≤ 1.74 :

). -Q2∙(2) + Y -1Y - q∙X2 = 0

Q2∙(2) =- Y - 1Y - q∙X2

Q2∙(0.231) = Y - 1Y - q∙X2 = 14.1 66.5 6.75 ∙ 0.231 = -53.95

Q2∙(1.74) = Y - 1Y - q∙X2 = -14.1 66.5 6.75 ∙ 1.74 = -64.145

). 2∙(2) - Y ∙(2)+ 1Y ∙(2 l1)+ 1 + q∙X2∙( X2/2) = 0

2∙(2) = Y ∙(2) - 1Y ∙(2 l1) - 1 - q∙X2∙( X2/2)

2∙(0.231) = Y ∙(2) - 1Y ∙(2 l1) - 1 - q∙X2∙( X2/2) = 14.1 ∙(0.231) -

- 68.5∙(0) -2.39 6.75∙0.231 ∙( 0.231/2) = -0.68

2∙(1.74) = - Y ∙(2)- 1Y ∙(2 l1)- 1 - q∙X2∙( X2/2) = 14.1 ∙(1.74) -

- 68.5∙(1.74) -2.39 6.75∙1.74∙( 1.74/2) = -88.4

). N1∙(2) - - 1 = 0

N1∙(2) = + 1 = 234.1

1.74 ≤ 3 ≤ 2.52 :

). -Q3∙(3) + Y - 1Y - q∙X3 = 0

Q3∙(3) = Y - 1Y - q∙X3

Q3∙(1.75) = Y - 1Y - q∙X3= 14.1 66.5 -6.75∙1.74 = -64.14

Q3∙(2.52) = = Y - 1Y - q∙X3= 14.1 66.5 -6.75∙2.52 = -69.41

). 3∙(3) - Y ∙(3)+ 1Y ∙(3 l1)+ 1 + 2 + q∙X3∙( X3/2) = 0

3∙(3) = Y ∙(3) - 1Y ∙(3 l1) - 1 - 2 - q∙X3∙( X3/2)

3∙(1.74) = 14.1 ∙(1.74) 66.5∙(1.74 0.231) 2.39 - 79.3-6.75∙2.52(1.74/2) = -167.37

3∙(2.52) = 14.1 ∙(2.52) 66.5∙(2.52 0.231) 2.39 - 79.3-6.75∙2.52 (2.52/2) = -219.8

). N3∙(3) - - 1 +2Y = 0

N3∙(3) = +1 -2Y = -4.5

2.52 ≤ 4 ≤ 2.7 :

). -Q4∙(4) + Y - 1Y +3Y - q∙X4 = 0

Q4∙(4) = Y - 1Y +3Y - q∙X4

Q4∙(2.52) = 14.1 -66.5+483.3-6.75∙2.52 = 413.89

Q4∙(2.7) = 14.1 -66.5+483.3-6.75∙2.7 = 412.89

). 4∙(4) - 3 + 1+2 Y ∙(4) + 3Y ∙(-l1-l2) + q∙X4 ∙( X4/2) +

+ 1Y ∙(-l1) = 0

4∙(4) = 3 - 1-2 + Y ∙(4) - 3Y ∙(-l1-l2) - q∙X4 ∙( X4/2) - 1Y ∙(-l1)

4∙(2.52) =133.2 2.39 79.3 -6.75∙2.52 (2.52/2)+ 14.1 ∙2.52 66.5∙(2.52 0.231) +0 = -86.61

4∙(2.7) = 133.2 2.39 79.3 -6.75∙2.7 (2.7/2)+ 14.1 ∙2.7 66.5∙(2.7 0.231) + 483.3∙(2.7 0.231) = - 12.2

). N4∙(4) - - 1 +2Y + 3Y = 0 N4∙(4) = +1 -2Y - 3Y = -252.73

: 1 2 3 4 5 6

Copyright 2018 - All Rights Reserved - www.transportbasis.ru